Motor asymmetry in elite fencers - Akpinar, S.; Sainburg, R. L.; Kirazci, S.; Przybyla, A. (Journal of Motor Behavior, 2015)
The authors previously reported that asymmetrical patterns of hand preference are updated and modified by present sensorimotor conditions. They examined whether participation in long-term training in the upper extremity sport fencing might modify arm selection and performance asymmetries. Eight fencers and eight nonfencers performed reaching movements under 3 experimental conditions: (a) nonchoice right, (b) nonchoice left, and (c) choice, either right or left arm as selected by subject. The nonchoice conditions allowed assessment of potential interlimb differences in movement performance, while the choice condition allowed assessment of the frequency and pattern of arm selection across subject groups. Our findings showed that the athlete group showed substantially greater symmetry in the performance and selection measures. These findings suggest that arm selection and performance asymmetries can be altered by intense long-term practice.